Inorganic perovskite-based active multifunctional integrated photonic devices - Qi Han; Jun Wang; Shuangshuang Tian; Shen Hu; Xuefeng Wu; Rongxu Bai; Haibin Zhao; David W. Zhang; Qingqing Sun; Li Ji (Nature Communications, 2024)
Abstract The development of highly efficient active integrated photonic circuits is crucial for advancing information and computing science. Lead halide perovskite semiconductors, with their exceptional optoelectronic properties, offer a promising platform for such devices. In this study, active micro multifunctional photonic devices were fabricated on monocrystalline CsPbBr3 perovskite thin films using a top-down etching technique with focused ion beams. The etched microwire exhibited a high-quality micro laser that could serve as a light source for integrated devices, facilitating angle-dependent effective propagation between coupled perovskite-microwire waveguides. Employing this strategy, multiple perovskite-based active integrated photonic devices were realized for the first time. These devices included a micro beam splitter that coherently separated lasing signals, an X-coupler performing transfer matrix functions with two distinguishable light sources, and a Mach-Zehnder interferometer manipulating the splitting and coalescence of coherent light beams. These results provide a proof-of-concept for active integrated functionalized photonic devices based on perovskite semiconductors, representing a promising avenue for practical applications in integrated optical chips.